Neither quantification by qPCR nor quantitative Elisa can be used to discriminate Angus cattle for resistance/susceptibility to Babesia bovis - Giglioti, Rodrigo [UNESP]; Oliveira, Henrique Nunes [UNESP]; Guaratini Lbelli, Adriana Mercia; Bilhassi, Talita Barban [UNESP]; Neo, Thalita Athie; Santana, Clarissa Helena [UNESP]; Rabelo, Marcio Dias; Machado, Rosangela Zacarias [UNESP]; Souza Chagas, Ana Carolina de; Sena Oliveira, Marcia Cristina de (Elsevier B.V., 2017)
With the aim of finding quantitative phenotypic traits that can be used to discriminate the levels of resistance/susceptibility to Babesia bovis, we estimated the repeatability and correlation between the level of infection, determined by the number of copies of a fragment of the gene that encodes cytochrome B (NC mt-cyB) of B. bovis, and the levels of the anti-B. bovis antibodies, in blood samples collected from 51 Angus cattle on two different occasions. Samples with the anticoagulant EDTA were used for DNA extraction and without anticoagulant for separation of the blood serum. The quantification of the NC mt-cyB of B. bovis was carried out by the quantitative PCR technique (qPCR), while the anti-B. bovis IgG antibody titers (S/P) were quantified by the ELISA method. The NC and S/P data were log10-transformed to improve the approximation to the normal distribution and were analyzed using mixed models. The correlations between NC mt-cyB and S/P were estimated, as well as the repeatability values for each trait. The results obtained showed the high sensitivity of the techniques, with 100% of the animals being positive for B. bovis, detected by both the serological and molecular tests. The correlations estimated between NC and S/P were low, 0.10 and 0.12, in the first and second collection, respectively. The repeatability estimated for NC was 0.06, whereas for the SIP it was 0.42. The low correlations between S/P and NC in the two collections demonstrated that the variation in the NC value is independent of the level of antibodies. This results indicated that animals with a higher levels of antibodies against B. bovis in the first collection continued to have a higher levels in the second one. However, the very low values for the repeatability value of NC, and for the correlations between S/P and NC, demonstrates that neither NC or S/P could be used to discriminate animals for resistance/susceptibility to B. bovis. (C) 2016 Elsevier GmbH. All rights reserved.
Keywords: Babesia bovis; Beef cattle; Resistance; Repeatability; Correlations